Tbp and Hprt1 Are Appropriate Reference Genes for Splenic Neutrophils Isolated from Healthy or Tumor-Bearing Mice - Khetam Sounbuli; Ludmila A. Alekseeva; Aleksandra V. Sen’kova; Innokenty A. Savin; Marina A. Zenkova; Nadezhda L. Mironova (Biomedicines)
Background/Objectives: Neutrophils have recently gained significant attention due to their heterogeneity in tumor settings. The gene expression profiles of neutrophils from different tumor types are of great interest. Murine splenic neutrophils reflect the immune status of the organism and could be a source of tumor-associated neutrophils in tumor-bearing mice. However, information about appropriate reference genes for RT-qPCR analysis of murine neutrophils in the literature is lacking. The aim of this study was to identify stably expressed reference genes in murine splenic neutrophils. Methods: Bone marrow- and spleen-derived neutrophils were isolated from healthy C57Bl/6 and CBA/LacSto mice. Spleen-derived neutrophils were isolated from mice with Lewis lung carcinoma (LLC) and drug-resistant lymphosarcoma (RLS40). RNA was isolated and used for RT-qPCR analysis of 10 selected reference genes. Analysis of reference gene stability was performed using four different algorithms (BestKeeper, NormFinder, geNorm, ΔCt method), and comprehensive ranking was constructed using RefFinder. Results: The Ct values for the reference genes were in the range of 16.73–30.83 with the highest expression levels observed for B2m and the lowest for Sdha. Differences in the stability ranking performed by different algorithms were observed; however, the overall ranking of the studied reference genes was as follows, from most to least stably expressed: Tbp, Hprt1, Ywhaz, B2m, Gapdh, Actb, Sdha, Eef2, Rack1, and Rpl13a. Using Tbp or Rpl13a for RT-qPCR data normalization significantly affected the interpretation of target gene expression. Conclusions: Tbp and Hprt1 are recommended reference genes for murine splenic neutrophils regardless of their activation status.